Study the Optical Properties of AI-doping in ZnO Thin Film Grown by Sol-gel Spin Coating Technique - Gurung, Anil Kumar; Ghimire, Rishiram; Chaudhary, Om Naryan; Acharya, Dipak Kumar (Journal of Physical and Life Sciences, 2024)
The study explored the effects of aluminum doping on the optical and electrical properties of ZnO thin films, along with their gas-sensing capabilities, specifically in response to blood serum. ZnO thin films were prepared using a spin-coating method, followed by annealing at 400C, with varying Al doping concentrations (0%, 1%, 2%, 3%, 4%, and 5%). In this work, we investigate the influence of Al doping on ZnO to detect various concentrations of acetone vapor. It was found that the optical band gap of Al-ZnO varies from 3.045 eV to 3.385 eV, and the aluminium concentration in ZnO films increased from 0% to 5%. Optical properties have been studied, and the observed band gap lies in the range of (3.045 - 3.385) eV. The 1% Al-ZnO sample showed a better response than the undoped ZnO film. The increase in the percentage of dopant i.e., Aluminium in the ZnO thin film, the sensitivity was somewhat increased. Time-dependent drift in resistance of ZnO films has been observed. ZnO films showed a fast and slow resistance change response when exposed to gases with varying volumes. The maximum values of sensitivity in terms of resistance were found to be 199.20 for doped and 189 for Al-doped and undoped ZnO thin film for 3 ml volume. The decreased resistivity with increasing Al concentration may be attributed to an increase in both carrier concentration and Hall mobility.